Constrained sintering of BaLa4Ti4O15 thick films: Pore and grain anisotropy - Amaral, Luis
Constrained sintering of BaLa4Ti4O15 (BLT) thick films on flexible platinum foil and on rigid BLT substrate showed enhanced grain growth and anisotropic microstructure development when compared with bulk samples having similar green packing and sintered under the same conditions. The evolution of the microstructural parameters (grain and pore shape, orientation) during densification and their correlation was investigated in films and compared with the morphological evolution in bulk samples. It is then expected that the appropriate choice of substrate will allow designing tailored microstructures of functional thick films with optimized performance. (C) 2013 Elsevier Ltd. All rights reserved.